The Role of WHO in Increasing Mental Health Awareness in South Korea in 2016-2019 - KURNIAWAN, Muhammad Okva Virandika; JUNED, Mansur (International Journal of Environmental, Sustainability, and Social Science, 2024)
Mental health is one of the main concerns for the World Health Organization (WHO). In 2012, the WHO announced that the most common mental health disorder affecting the global community is depression and the disease is a top priority to be treated globally in the context of mental health. South Korea is one of the UN member countries with a high death rate due to suicide due to depression. Although the prevalence of depression in South Korea has been reported to be much lower than in other countries, it is undeniable that every time South Korea is mentioned, the words "suicide", "depression" and "mental health" come to mind that remind us of the country of ginseng. This research aims to find out about what is the role of WHO to increase mental health awareness in South Korea in 2016-2019. This research use case study method and by delivering the findings descriptively. The results is the role of WHO in South Korea are providing WHO Mental Health Action Plan 2013–2020 as the technical guidance, to put WHO-AIMS in South Korea, The Mental Health Atlas publication, the WHO Collaborating Centre for Psychosocial Rehabilitation and Community Mental Health in Yongin Mental Hospital, the Depression: Let's Talk campaign, and the WHO Special Initiative in handling mental health, namely The WHO Special Initiative for Mental Health (2019-2023): Universal Health Coverage for Mental Health in 2019.